Adenovirus VA RNAI Blocks ASC Oligomerization and Inhibits NLRP3 Inflammasome Activation - Darweesh, Mahmoud; Kamel, Wael; Gavrilin, Mikhail A.; Akusjärvi, Göran; Svensson, Catharina (Frontiers in Immunology, 2019)
Virus infected immune cells can rapidly respond to the invader by activating the inflammasome and as a consequence release proinflammatory cytokines and eventually die by pyroptosis. In human adenovirus-5 (Ad5) infected THP-1 cells, inhibition of NLRP3 inflammasome activation was demonstrated by a decreased secretion of HMGB1 and matured forms of caspase-1and IL-1ß. An Ad5 mutant virus defective in expression of the non-coding VA RNAI failed to inhibit the NLRP3 inflammasome and in addition displayed formation of ASC specks and increased cell lysis. This inhibition of NLRP3 inflammasome activation required the phylogenetically conserved central stem of VA RNAI, which is required for VA RNAI to efficiently bind and inhibit activation of PKR. Importantly, in vitro synthesized VA RNAI was able to inhibit the NLRP3 inflammasome activity in THP-1 cells in the absence of an Ad5 infection, suggesting that VA RNAI binding to PKR and blocking its function is sufficient for inhibition of the NLRP3 inflammasome. We show that VA RNAI did not affect PKR interaction with NLRP3. In contrast, we describe a novel interaction between PKR and ASC and further show that VA RNAI inhibited ASC phosphorylation and oligomerization. Collectively, our results indicate a novel role for Ad5 VA RNAI as an inhibitor of NLRP3 inflammasome activation by targeting the cellular pro-inflammatory protein PKR.